Optimizing Continuous Delivery Pipelines for Faster Time-to-Market - Vidyasagar Vangala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
In the modern competitive software development environment, speed with quality is a decisive advantage. Continuous Delivery pipelines are a must to have for frequent and predictable software releases; however, most organizations fail to optimize the Continuous Delivery pipelines for quicker time-to-market. This article looks at some ways to improve the efficiency of the CD pipeline on aspects related to automation, integration, and testing. Topics under discussion will include how smoothed workflows, parallel processing, and intelligent monitoring tools play their role in achieving deployment cycles with high standards of quality and stability in shorter duration. It also points out the best practices for managing infrastructure as code, optimizing version control processes, and promoting effective collaboration between the development, operation, and quality assurance teams. Application of these techniques would speed up the release cycle and enhance product quality to meet the market requirements much faster.